Penerapan Model Pembelajaran Teams Games Turnament (TGT) Pendidikan Agama Islam dalam Meningkatkan Prestasi Belajar Siswa Kelas V Sekolah Dasar Negeri 2 Mangun Jaya Sirah Pulau Padang - Riyanto, Idwin; Aryati, Ani; Sua’idi, Ruskam (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2021)
The purpose of this study was to determine the learning model of the Teams Games Turnament (TGT) for Islamic Religious Education in improving the learning achievement of the fifth grade studens of public elementary school 2 Mangun Jaya Sirah Pulau Padang. The Teams Games Turnament learning model aims to describethe problem faced such as how the application of the Teams Games Turnament learning of islamic Religious Education in improving student learning achievement in grade v, what are the inhibiting and supporting factros for the application of the learning model type Teams Games Turnament islamic Religious education in improving student learning achievement class v, how are you the learning achievement model for class v students. Teams Games Turnament. Is an alternative to overcome learning problems that have been considered ineffective, such as lack of otimal communication between students, low understanding of students’ concepts, students are bored with monotonous learning models so that students tend to be more passive in class. The type of research is qualitative and the data used is primary data in the from of data collected by students and secondary data is data from refence books that complement wxisting document. That data collection method used in this research is observation, interview and documentation. The results of this study indicate that there is a learning model of the Teams Games Turnament of islamic religious education in improving the learning achievement of grade v students of public elementary school 2 Mangun Jaya Sirah Pulau Padang.